The α-globin super-enhancer acts in an orientation-dependent manner - Mira T. Kassouf; Helena S. Francis; Matthew Gosden; Maria C. Suciu; Damien J. Downes; Caroline Harrold; Martin Larke; Marieke Oudelaar; Lucy Cornell; Joseph Blayney; Jelena Telenius; Barbara Xella; et al. (Nature Communications)
Abstract Individual enhancers are defined as short genomic regulatory elements, bound by transcription factors, and able to activate cell-specific gene expression at a distance, in an orientation-independent manner. Within mammalian genomes, enhancer-like elements may be found individually or within clusters referred to as locus control regions or super-enhancers (SEs). While these behave similarly to individual enhancers with respect to cell specificity, distribution and distance, their orientation-dependence has not been formally tested. Here, using the α-globin locus as a model, we show that while an individual enhancer works in an orientation-independent manner, the direction of activity of a SE changes with its orientation. When the SE is inverted within its normal chromosomal context, expression of its normal targets, the α-globin genes, is severely reduced and the normally silent genes lying upstream of the α-globin locus are upregulated. These findings add to our understanding of enhancer-promoter specificity that precisely activate transcription.